An Optimized Indoor RFID Positioning System Using 3D Mobility Pattern - REZA, A. W.; RUI, T. T.; KAUSAR, A. S. (Advances in Electrical and Computer Engineering, 2014)
Radio frequency identification (RFID) is the widely used identification system that uses radio frequency for the detection of object position. A new RFID technique for the localization of tags in a 3D space is presented in this study. According to this technique, the optimized number of mobile readers is needed to afford full coverage within a given period of time. The mobile readers are programmed in such a way that they move in a zigzag pattern for detecting the tags. The received signal strength (RSS) model is used for determining the tag positions. From the obtained results, it can be observed that the proposed model can achieve an average error distance as low as 0.27 m for a given scenario and if the obstacles are placed in the test environment, the average error distance has only increased to 0.38 m. In order to evaluate the accuracy of the proposed technique, a comparison between the existing and proposed model is presented.